Estudio de las propiedades termodinámicas del sistema semilla-atmósfera mediante modelos de equilibrio higroscópico. - Socorro, A.; Vega, M.; Calderón, S. (Revista Cubana de Física, 2010)
Values of seed equilibrium moisture content regarding relative humidity from exterior atmosphere on two plant species were fitted. Three hygroscopic equilibrium models were used for the isothermic curves simulation for different temperatures. From these data, the enthalpy, Gibbs free energy and entropy were calculated to analyze the behaviour of these magnitudes with sorption properties of seeds.